Assessment of disorders in pelvic symmetry in 8-year-old children - Kurzeja, Piotr; Szurmik, Tomasz; Majerski, Piotr; Prusak, Jarosław; Mrozkowiak, Mirosław (Journal of Education, Health and Sport, 2018)
Introduction and purpose of the work The pelvis, constituting an element of the biokinematic chain that connects the torso with the lower limbs, is an important link in the compensation of the asymmetry appearing in these parts of the body. The asymmetrical position of the pelvis may have a static or functional basis, may affect postural disorder, contribute to the development of lateral curvature or result. The aim of the study was to assess the symmetry of the pelvic position and determine the relationship between spatial arrangement of the pelvis and the results of the Derbolowsky test.Material and methodThe research covered a group of 60 children aged 8 from primary schools of the Małopolska province. The study consisted of 3 parts: clinical assessment of the spine and posture, performance of the Derbolowsky test, examination of the trunk by topography of the body surface in a standing position.ResultsComparison of the obtained results of the difference in the length of the lower limbs in relation to the pelvic angle turned out to be statistically significant for both boys, girls and the general population. The analysis showed that in the examined group the increase in the pelvic angle by 1 degree corresponds to the increase in the difference in the length of the lower limbs by 0,36 centimeter. Differences in the pelvic angle with the Derbolowsky test values were different for groups of boys and girls, as were differences in the length of the lower limbs with the Derbolowsky test values.ConclusionsDerbolowsky test is one of the most effective tests that differentiate pelvic torsion and skewness. The scale of pelvic torsion in children is high.